Assessment of selected metals (chromium, lead and cadmium) in the hair of tannery workers at Hemayetpur, Bangladesh - Nurjahan Akter Shimo; Md. Abdus Salam; Maksuda Parvin; Md. Zakir Sultan (Journal of Trace Elements and Minerals, 2023)
Background: The goal of this study was to measure the concentrations of chromium (III) (Cr), lead (Pb), and cadmium (Cd) in the scalp hair of tannery workers. It also sought to establish a correlation between the levels of these metals and the length of time the workers had been employed. High level of exposures of these metals are associated with several diseases. Methods: Human hair samples from 18 tannery workers at Hemayetpur, Savar, Bangladesh, were collected and evaluated for metals (Cr, Pb, and Cd) using the Atomic Absorption Spectrophotometric technique (AAS). Results: The findings showed that the concentrations of chromium (III) (Cr), lead (Pb), and cadmium (Cd) in hair samples from tannery workers were ranged between 0.25 to 19.85 mg kg−1 (average value 6.254 mg kg−1), 0.50 to 9.25 mg kg−1 (average value 3.873 mg kg−1), and 0.025 to 0.20 mg kg−1 (average value 0.044 mg kg−1), respectively. Conclusion: In comparison to the allowable limits, there were appreciably high levels of chromium and lead, and low levels of cadmium. A positive correlation was also obtained between Cr-Cd pair from Pearson's correlation study. The results of the investigation suggest that the tannery workers had very high levels of chromium in their hair samples that indicated their hazardous working circumstances induced to their numerous illnesses, including high blood pressure, skin infections, and respiratory disorders.